2006
DOI: 10.1002/jrs.1623
|View full text |Cite
|
Sign up to set email alerts
|

The hydrates and deuterates of ferrous sulfate (FeSO4): a Raman spectroscopic study

Abstract: A comparative analysis has been carried out on the Raman spectra of FeSO 4 ·nH 2 O (n = 1, 4, 7) including the 2 D-analogs. The effects of changing the degrees of hydration have been found from the lattice, SO 4 2− internal, and H 2 O internal modes. Increasing degrees of hydration shift the intense n 1 (SO 4 ) peak to lower wavenumbers and reduce the amount of splitting on the n 3 (SO 4 ) peaks. Some of the water librational bands cause the broadening of the n 4 (SO 4 ) peaks in FeSO 4 ·7H 2 O and the n 2 (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 68 publications
5
42
0
1
Order By: Relevance
“…The H 2 O molecules at the ten crystallographically distinct sites in copiapite [42,43] give rise to Raman peaks at slightly different wavenumbers, and these H 2 O peaks overlap to form the broad band in the 3000-3700 cm −1 region. This overlap may be removed at lower temperature following the trend reported in the interesting studies by Chio et al [55,56] A diagnostic (sharp) Raman peak of the stretching vibrational mode of (OH) − group occurs near 3522 cm −1 for trivalent copiapite species and near 3528 cm −1 for divalent species as indicated by the dashed line in Fig. 4(a).…”
Section: Changes In Raman Spectral Features Caused By Cation Substitumentioning
confidence: 82%
“…The H 2 O molecules at the ten crystallographically distinct sites in copiapite [42,43] give rise to Raman peaks at slightly different wavenumbers, and these H 2 O peaks overlap to form the broad band in the 3000-3700 cm −1 region. This overlap may be removed at lower temperature following the trend reported in the interesting studies by Chio et al [55,56] A diagnostic (sharp) Raman peak of the stretching vibrational mode of (OH) − group occurs near 3522 cm −1 for trivalent copiapite species and near 3528 cm −1 for divalent species as indicated by the dashed line in Fig. 4(a).…”
Section: Changes In Raman Spectral Features Caused By Cation Substitumentioning
confidence: 82%
“…These changes in the spectrum suggest dehydration of FeSO 4 · 7H 2 O to FeSO 4 · 4H 2 O (rozenite). In the room-temperature micro-Raman spectrum of FeSO 4 · 4H 2 O, n 1 (SO 4 ) is observed at 990 cm −1 (Chio et al 2007). In addition, the Raman lines at 1284 and 1388 cm −1 of the Fermi doublet of CO 2 and weak shoulders at 1265 and 1409 cm −1 are also visible in the spectrum measured under sc-CO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…Ibáñez et al 130 studied the hydration and carbonation of monoclinic C 2 S and C 3 S, and Chio et al 131 Sudheer et al 135 reported on the characterization of laser processing of single-crystal natural diamonds using micro-Raman spectroscopy. These workers concluded that the surface quality of single-crystal diamonds is superior when extremely high-peak powers are employed in the laser cutting process.…”
Section: Other Inorganic Materialsmentioning
confidence: 99%